VMATc: VMAT with constant gantry speed and dose rate. (19th March 2015) - Peng, Fei; Jiang, Steve B; Romeijn, H Edwin; Epelman, Marina A
Abstract: This article considers the treatment plan optimization problem for Volumetric Modulated Arc Therapy (VMAT) with constant gantry speed and dose rate (VMATc). In particular, we consider the simultaneous optimization of multi-leaf collimator leaf positions and a constant gantry speed and dose rate. We propose a heuristic framework for (approximately) solving this optimization problem that is based on hierarchical decomposition. Specifically, an iterative algorithm is used to heuristically optimize dose rate and gantry speed selection, where at every iteration a leaf position optimization subproblem is solved, also heuristically, to find a high-quality plan corresponding to a given dose rate and gantry speed. We apply our framework to clinical patient cases, and compare the resulting VMATc plans to idealized IMRT, as well as full VMAT plans. Our results suggest that VMATc is capable of producing treatment plans of comparable quality to VMAT, albeit at the expense of long computation time and generally higher total monitor units.